2016
DOI: 10.1186/s13578-016-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Misregulation of the proline rich homeodomain (PRH/HHEX) protein in cancer cells and its consequences for tumour growth and invasion

Abstract: The proline rich homeodomain protein (PRH), also known as haematopoietically expressed homeobox (HHEX), is an essential transcription factor in embryonic development and in the adult. The PRH protein forms oligomeric complexes that bind to tandemly repeated PRH recognition sequences within or at a distance from PRH-target genes and recruit a variety of PRH-interacting proteins. PRH can also bind to other transcription factors and co-regulate specific target genes either directly through DNA binding, or indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 90 publications
1
28
0
Order By: Relevance
“…1,2 Hhex was first cloned via its expression in hematopoietic tissues, where it is highly expressed in hematopoietic stem cells (HSCs) and progenitors but then undergoes transcriptional downregulation during differentiation, particularly in the T-cell lineage. [3][4][5] Consistent with the function of members of the homeobox gene family, Hhex has been shown to have important developmental roles during embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Hhex was first cloned via its expression in hematopoietic tissues, where it is highly expressed in hematopoietic stem cells (HSCs) and progenitors but then undergoes transcriptional downregulation during differentiation, particularly in the T-cell lineage. [3][4][5] Consistent with the function of members of the homeobox gene family, Hhex has been shown to have important developmental roles during embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these mechanisms are likely to contribute to the induction of EMT and to be of relevance in prostate cancer progression. As PRH appears to function as a tumour suppressor in breast cancer cells and some other cancer cells 18 , it is likely that some or all of these mechanisms are important in the context of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor PRH/HHEX (proline-rich homeodomain/haematopoietically expressed homeobox) is essential for the formation of many organs during embryonic development 16,17 . PRH is expressed in many tissues in the adult and downregulation of PRH protein expression and/or aberrant subcellular localisation of PRH is associated with breast, prostate, thyroid, and liver tumours 18 . PRH inactivation is common to a number of cancer types but the mechanisms of PRH inactivation vary in different disease states.…”
Section: Introductionmentioning
confidence: 99%
“…Like many transcription factors PRH can either repress or activate transcription depending on its target gene (see Soufi et al [1] and Gaston et al [40] for lists of PRH target genes) and its partner proteins (shown in Figure 1). For example, PRH represses the Goosecoid, ESM-1, VEGFA, VEGFR-1, VEGFR-2, and thyroglobulin promoters [8,21,23,24].…”
Section: The Regulation Of Gene Expressionmentioning
confidence: 99%
“…In contrast, PRH has been shown to function as an oncoprotein in T-cell lineages and in AML subtypes (reviewed by Gaston et al [40]). In retroviral insertion experiments in mice (Lvis1)-elevated PRH expression is associated with B-cell-and T-cell-derived leukaemias and lymphomas [41,42].…”
Section: Prh Activity In Tumourigenesismentioning
confidence: 99%